Role of TPBG (Trophoblast Glycoprotein) Antigen in Human Pericyte Migratory and Angiogenic Activity. Issue 6 (June 2019) - Spencer, Helen L.; Jover, Eva; Cathery, William; Avolio, Elisa; Rodriguez-Arabaolaza, Iker; Thomas, Anita C.; Alvino, Valeria V.; Sala-Newby, Graciela; Dang, Zexu; Fagnano, Marco; Reni, Carlotta; Rowlinson, Jonathan; et al.
Abstract : Objective—: To determine the role of the oncofetal protein TPBG (trophoblast glycoprotein) in normal vascular function and reparative vascularization. Approach and Results—: Immunohistochemistry of human veins was used to show TPBG expression in vascular smooth muscle cells and adventitial pericyte-like cells (APCs). ELISA, Western blot, immunocytochemistry, and proximity ligation assays evidenced a hypoxia-dependent upregulation of TPBG in APCs not found in vascular smooth muscle cells or endothelial cells. This involves the transcriptional modulator CITED2 (Atypical chemokine receptor 3 CBP/p300-interacting transactivator with glutamic acid (E)/aspartic acid (D)-rich tail) and downstream activation of CXCL12 (chemokine [C-X-C motif] ligand-12) signaling through the CXCR7 (C-X-C chemokine receptor type 7) receptor and ERK1/2 (extracellular signal-regulated kinases 1/2). TPBG silencing by siRNA transfection downregulated CXCL12, CXCR7, and pERK (phospho Thr202/Tyr204 ERK1/2) and reduced the APC migratory and proangiogenic capacities. TPBG forced expression induced opposite effects, which were associated with the formation of CXCR7/CXCR4 (C-X-C chemokine receptor type 4) heterodimers and could be contrasted by CXCL12 and CXCR7 neutralization. In vivo Matrigel plug assays using APCs with or without TPBG silencing evidenced TPBG is essential for angiogenesis. Finally, in immunosuppressed mice with limb ischemia, intramuscular injection of TPBG-overexpressing APCs surpassed naïve APCs in enhancing perfusion recovery and reducing the rate of toe necrosis. Conclusions—: TPBG orchestrates the migratory and angiogenic activities of pericytes through the activation of the CXCL12/CXCR7/pERK axis. This novel mechanism could be a relevant target for therapeutic improvement of reparative angiogenesis. Abstract : Supplemental Digital Content is available in the text.